Iran's Nuclear Fatwa: Analysis of a Debate. Issue 3 (2nd July 2016) - Sabouri, Mohammad Hossein
ABSTRACT: For more than a decade, Iran has been referring to a fatwa issued by its Supreme Leader, Ali Khamenei, proscribing nuclear weapons. The fatwa, however, not only failed to influence the process that led to the resolution of Iran's nuclear crisis, but also has been met with a good deal of skepticism. The most commonly held suspicions about the credibility of the fatwa can be summed up in five central questions: (1) Has the nuclear fatwa actually been issued? (2) Does the fatwa apply to all the aspects of nuclear weapons including their production, possession and use? (3) What is the juridical status of the fatwa? (4) Was the nuclear fatwa issued only to deceive other nations? (5) Is the fatwa really irreversible? This article tries to answer these questions by providing a chronological review of the fatwa and analyzing all the relevant statements by Khamenei. The analysis is conducted against the background of Islamic principles, Shi'a jurisprudence and the history of the Islamic Republic of Iran. The article concludes that the fatwa is a credible religious decree and could indeed contribute to the cause of nuclear disarmament.